PENGARUH JENIS BAHAN BAKAR GASOLIN TERHADAP PRESTASI, PEMBAKARAN, GETARAN, KEBISINGAN, DAN EMISI GAS BUANG PADA MESIN TYPE TV-1 - Andi Erwin Eka Putra; Nasruddin Aziz (Jurusan Teknik Mesin, Universitas Halu Oleo, 2021)
The growth of vehicles in Indonesia is dominated by motorcycles. The current compression ratio of the motorcycle is above 9 : 1. Types of gasoline on the market have octane number of 88, 90, 92. The purpose of this study is to analyze engine and combustion performance, noise and vibration, and emissions from gasoline type with a compression ratio of 10 : 1. This study was used engine with 1 cylinder and 4 strokes, sound level meter to measure noise, VibexpertII with acceleration mode for vibration measurement, AGS-688 for exhaust emission test. The test results showed that the break power of all fuels tends to be constant and the smallest SFC is an octane number of 92 (ON 92). The combustion performance of ON 92 also tends to be stable, but noise and vibration of ON 92 are higher. CO and HC emissions of all fuel tend to be constant.